A7.15 in vitro silencing of HNRNP-A2/B1 in synovial fibroblasts reveals involvement in regulation of several signal transduction pathways. (24th February 2016) - Fischer, A; Herman, S; von Dalwigk, K; Kiener, H; Steiner, G
Abstract : Background and objectives: The heterogeneous nuclear ribonucleoprotein (hnRNP) A2/B1 is involved in post-transcriptional regulation of gene expression. It has been shown to be highly upregulated in synovial tissue of patients with rheumatoid arthritis (RA). In addition, autoantibodies and T cells directed against hnRNP-A2/B1 can be found in RA patients. Recently, it was shown that silencing of hnRNP-A2/B1 in two animal models of RA, namely Collagen-induced arthritis and K/BxN serum transfer arthritis, led to reduction of arthritis severity. 1 To further elucidate the role of hnRNP-A2/B1 in RA, we sought of analysing the signalling pathways affected by silencing of hnRNP-A2/B1 in human fibroblast-like synoviocytes (FLS). Materials and methods: siRNA-mediated silencing of hnRNP-A2/B1 in FLS was achieved by lipofectamine-based transfection. After three days, successful reduction of hnRNP-A2/B1 expression was analysed by real-time quantitative polymerase chain reaction (RT-qPCR). The role of hnRNP-A2/B1 in FLS was investigated by activating cells with TNF-α. Proteome Profiler Arrays were used to analyse cytokine production and phosphorylation of various signal transduction molecules. Interleukin (IL) -6 and IL-8 secretion was assayed using enzyme-linked immunosorption assay (ELISA). Results: Silencing of hnRNP-A2/B1 led to a reduction of phosphorylation of AKT and mammalian target of rapamycin (mTOR) in TNF-α stimulated cells and a slight reduction in phosphorylation of p70 S6 kinase, which is a downstream signalling component of mTOR. Moreover, down-regulation of hnRNP-A2/B1 led to reduced levels of phosphorylated MAPK14 (p38α), and a reduction of MSK2 phosphoryl ation. Analysis of supernatants revealed reduced levels of CCL5 (RANTES), CXCL10 (IP-10), CCL20 (MIP-3α) and Serpine E1, but increased levels of ICAM-1. In addition, reduced secretion of Dickkopf-1 (DKK-1) or IGFBP-3 could be detected in silenced cells. Surprisingly, secretion of IL-6 and IL-8 was slightly increased in hnRNP-A2/B1 silenced FLS. Conclusions: hnRNP-A2/B1 seems to play an important role in regulation of several signalling pathways, mainly the mTOR pathway, which is involved in translation and cell growth. Further analyses will be needed to fully understand the role of hnRNP-A2/B1 in signalling pathways operative in FLS and other inflammatory cell types involved in the pathogenesis of RA. Reference: Herman S, et al . Inhibition of Inflammation and Bone Erosion by RNA Interference-Mediated Silencing of Heterogeneous Nuclear RNP A2/B1 in Two Experimental Models of Rheumatoid Arthritis. Arthritis Rheumatol 2005;67:2536–46